Tribological behavior of polyethylene for biomedical material - Neo, Li Ping (2013)
The study of tribology on artificial hip joint bearing surfaces has been carried out for many decades. The analysis of the tribological interactions at the bearing surfaces gave researchers many insights as to which combinations of materials used were suitable for the application. With an expected service life of around 25 years on most devices, and with younger and younger patients undergoing this surgery, it is of great importance to investigate on the tribology on hip joint bearing surfaces.